A second-best solution to higher education challenges - Jordaan, Yolanda; van Heerden, Gene; Jordaan, Andre C (South African Journal of Higher Education, 2018)
Higher education educators are experiencing challenges and increasing pressure to ensure that graduates are employable. Some speculate that the lack of the right employment skills could contribute even more to the increase in unemployment, than does the global recession. There is a belief that a relationship exists between secondary education, tertiary education and industry, as role-players in providing the necessary skills-training for employment. This relationship seems to be linear, and when an imbalance in any of these environments occurs, it could potentially have an effect on the overall economic wellbeing of the specific country. This paper explores the challenges experienced by higher education educators with regard to student employability. The theory of the second best is introduced, as a possible solution to address the educational challenges. Intervention strategies are proposed, specifically from a marketing educator’s perspective.